DESAIN PRODUK STAND HOLDER HANDPHONE - Febriyana, Vina; Ramadhan, Muhamad; Yunus, Muhammad; Haritsah Amrullah, Muhammad (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Mobile phone users in Indonesia have currently reached 345 million units. Due to the large number of mobile phone users currently, some people may need a holder on their desk to make calls, watch videos and use applications without needing to hold the mobile phone directly. Product design for a cellphone stand holder with movement of at least 2 planes of rotation for use on a table. The aim of making this final project is to create a cellphone stand holder product design using Solidwork software and the product is printed using 3D printing in the Bangka Belitung State Manufacturing Polytechnic laboratory. This research uses the VDI2222 method, namely, planning, conceptualizing, designing, completing. The product will be produced in the Polman Babel mechanical laboratory using 3D printing. Cellphone stand holder products with sizes P=29mm, L=29mm, T=100mm are able to withstand a maximum load of 250 grams, with main systems such as a rotation system that uses a ball head that can rotate 360°, a holder and lock system that can clamp the cellphone holder when in use. , and the grounding system uses standard aluminum alloy materials. Holder was able to process 3D printing in 3.17 hours.